Treatment of Highly Drug-Resistant Pulmonary Tuberculosis - Conradie, Francesca; Diacon, Andreas H; Ngubane, Nosipho; Howell, Pauline; Everitt, Daniel; Crook, Angela M; Mendel, Carl M; Egizi, Erica; Moreira, Joanna; Timm, Juliano; McHugh, Timothy D; Wills, Genevieve H; et al. (The New England journal of medicine, 2020)
Treatment options for highly drug-resistant tuberculosis are limited. In this study in South Africa, a new agent, pretomanid, was combined with bedaquiline and linezolid for a 26-week course to treat extensively drug-resistant and complicated multidrug-resistant pulmonary TB. Although there were toxic effects, 90% of patients had favorable outcomes.